In Coconut Gardens... Vermicomposting from baby corn for more return - Gupta, Alka; Gopal, Murali; Maheswarappa, H P (Indian Horticulture, 2019)
Cultivation of baby corn as a component crop in coconut interspaces yields agro-residues in the form of baby corn stover after harvesting of cobs. The baby corn stover could be successfully converted to quality vermicompost using coconut leaf degrading epigeic earthworm, Eudrilus sp., available at CPCRI, Kasaragod. The baby corn stover vermicompost has 21% organic carbon, 2.3% nitrogen, 0.4% phosphorus and 0.4% potassium. The agro-wastes generated from coconut-based cropping system can be recycled within the farm for soil and plant health improvement.